PRESSURE TREATMENT OF EUCALYPTUS CAMALDULENSIS POLES WITH OIL - BORNE PRESERVATIVE - M. Uzzaman, Younus; Akhter, Khurshid (วารสารวนศาสตร์ไทย, 2022)
Eucalyptus cumaldulensis poles were treated with 50 : 50 creosote light diesel oil mixture, The pole size round E. camaldulensis was found to contain an average of 53.85 % sapwood, which is readily persihable by wood destroying organisms. Eucalypt poles were treated by the Bethel Full-Cell process using varying pressure and duration to evaluate the effect on penetration and retention of the preservative mixture. It was found that with the increase of both treating pressure and time, the increase in penetration was not found to be statistically significant. Only treating pressure had highly significant effect on increasing the retention of preservative in the sapwood. The coefficient of variations of penetration and retention within the individual poles and the same between the poles were calculated. A penetration of 3.5 cm with retention of 318.45 kg / m3 in the treated sapwood could be obtained by using 10.57 kg / cm2 pressure for 3 hrs. This penetration is considered adequate to protect the sapwood region of the pole.